Adverse reactions of four multi-targeted tyrosine kinase inhibitors: a descriptive analysis of the WHO-VigiAccess database - Li, Lijun; Bai, Jiayu; Wen, Xuelong; Zeng, Xuefan (Frontiers in Pharmacology, 2025)
BackgroundThe introduction of multi-targeted tyrosine kinase inhibitors (MTKIs) such as axitinib, lenvatinib, sorafenib, and sunitinib has greatly broadened the available treatment options for Renal Cell Carcinoma (RCC). The study aims to compare the nature of the adverse reactions associated with these four MTKIs to identify which medication poses the least risk for personalized patient management, thus enabling more accurate clinical drug oversight.MethodsEmploying a retrospective descriptive analysis methodology, this research concentrated on four commercially available MTKIs. Reports pertaining to these medications were sourced from the WHO-VigiAccess database. The data gathering process involved collecting comprehensive information on various parameters, such as age demographics, gender, and the geographical distribution of patients associated with the ADR reports. Furthermore, the study explored disease systems and symptoms that were documented alongside the adverse reactions, as outlined in the annual ADR reports produced by the WHO. To assess the relationship between these four MTKIs and the linked AEs, both the Proportional Reporting Ratio (PRR) and the Reported Odds Ratio (ROR) were utilized.ResultsAt the time of the search, a total of 123,818 AEs associated with the four MTKIs had been documented in the VigiAccess database. The common ADRs for these four MTKIs include diarrhoea, fatigue, death, hypertension, nausea, asthenia, weight decreased, and vomiting. Gastrointestinal disorders and general disorders and administration site conditions emerged as the SOCs with the highest number of adverse signals, both ranking first in terms of frequency. The elevated ROR (1.08) and PRR (1.06) values associated with gastrointestinal disorders in patients treated with sorafenib suggest a higher incidence of such adverse events compared to those observed with axitinib, lenvatinib, and sunitinib.ConclusionRecent comparative observational research suggests that the ADR reports submitted to the WHO and the FDA for these medications highlight both common and specific ADRs. It is essential for clinical practitioners to develop personalized treatment strategies that consider the adverse effects linked to different medications, alongside the unique circumstances of their patients, thus encouraging the responsible use of these MTKIs.